Формування вирішальної функції кореляційно-екстремальних систем навігації за критерієм максимуму узагальненого коефіцієнта взаємної кореляції - Єрьоміна, Наталія Сергіївна; Сотніков, Олександр Михайлович; Таршин, Володимир Анатолійович (НТУ "ХПІ", 2016)
Проведено аналіз впливу геометрії візування кореляційно-екстремальних систем навігації (КЕСН) на вирішальну функцію (ВФ), яка визначає точнісні характеристики системи. Встановлено, що найбільший вплив з геометричних спотворень на ВФ здійснюють перспективні спотворення. Запропоновано метод формування ВФ КЕСН, заснований на адаптації еталонних зображень (ЕЗ) до перспективних спотворень. Показана доцільність формування ЕЗ поверхні візування (ПВ) шляхом визначення максимуму коефіцієнта взаємної кореляції в кожному елементі розрізнення та побудови узагальненої взаємної функції кореляції.

The article deals with issues related to improving the correlation-extreme navigation systems by developing a method of forminga crucial function based on adaptation of reference images to perspective distortion depending on the viewing conditions in obtaining basic information about viewing surface. The research include: suggestions for improving the correlation-extreme navigation systems and increasing system performance. In scientific innovation first formulated and solved the problem of developing a method of forming the crucial function of correlation-extreme air navigation systems based on the adaptation of reference images to perspective distortion depending on the viewing conditions in obtaining basic information about viewing surface. Method wording set out an approach based on identifying cross-correlation coefficient maximum in each distribution building elements and functions of generalized cross correlation. The practical significance lies in the possibility of using the proposed method in designing and researching ways to improve value-extreme navigation systems of aircraft and their systems of recycling.
Creating a decision function correlation-extreme systems navigation on generalized criterion of maximum cross-correlation coefficient
Keywords: перспективні спотворення; еталонні зображення; поточні зображення; ПЗ; ВФ; безпілотні літальні апарати; БПЛА; critical function; perspective distortions; reference image